2019
DOI: 10.1155/2019/6292036
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Helium Inflating on Heat Dissipation and Luminescence Properties of the A60 LED Filament Lamps

Abstract: LED filament lamp has the characteristics of nearly 360° lighting angle, high brightness, and low energy consumption, turning it gradually into the best substitute for traditional incandescent lamps. At present, due to the limitations of heat dissipation, the development of high-power LED filament lamp is restricted. Helium is a rare gas with small density and high heat transfer coefficient. It can be used as a cooling and protective gas for LED filament lamp. In this paper, we investigated the effects of heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Hydrogen (0.163 W/m•K) would be better thermal conductor, but for other reasons not a suitable filling gas. [1] studied the possibility to reduce the ratio of helium gas while still maintaining sufficient heat dissipation characteristics. They found that the ratio of helium gas can be reduced to 80% when both luminous flux and color temperature still remains in a typical level.…”
Section: Thermal Management Of Filament Led Bulbsmentioning
confidence: 99%
“…Hydrogen (0.163 W/m•K) would be better thermal conductor, but for other reasons not a suitable filling gas. [1] studied the possibility to reduce the ratio of helium gas while still maintaining sufficient heat dissipation characteristics. They found that the ratio of helium gas can be reduced to 80% when both luminous flux and color temperature still remains in a typical level.…”
Section: Thermal Management Of Filament Led Bulbsmentioning
confidence: 99%